The Effect of Combined Exercise and Curcumin Supplementation on TCF-1 and GSK3β Gene Expression in the Brains of Rats with Glioblastoma Multiforme - S Afshar Yousefi; Y Kazemzadeh; H Shirvani; S Mirzayan Shanjani (Armaghane Danesh Bimonthly Journal)
Background & aim:  Lifestyle modification and the use of nanotechnology are considered therapeutic strategies for cancers. Therefore, the aim of the present study was to determine the effect of combined exercise and curcumin supplementation on the expression of T cell factor 1 (TCF-1) and glycogen synthase kinase 3 beta (GSK3β) genes in the brains of mice with glioblastoma multiforme.